A review on the pyrolysis of algal biomass for biochar and bio-oil – Bottlenecks and scope. (1st January 2021) - Sekar, Manigandan; Mathimani, Thangavel; Alagumalai, Avinash; Chi, Nguyen Thuy Lan; Duc, Pham Anh; Bhatia, Shashi Kant; Brindhadevi, Kathirvel; Pugazhendhi, Arivalagan
Highlights: Analyzing the recent developments in pyrolysis processes of microalgae. Mechanism of the various types of pyrolysis was summarized. Biochemical composition was discussed in detail. Microwave assisted pyrolysis has achieved more significance than other process. Quality of the bio-oil in catalytic pyrolysis was higher than thermal pyrolysis. Abstract: Algae become reasonable feedstock in recent times for biofuel production as they are environmentally benign, sustainable and renewable biomass. Biofuels are produced from algal biomass by chemical, biochemical, and thermochemical methods. Among the thermochemical techniques, pyrolysis is a well-known method involving high temperature and high pressure to produce biochar and bio-oil from numerous algal biomasses. Therefore, this review was undertaken to collate and discuss different pyrolytic processes employed for the conversion of algal biomass into biochar and bio-oil production. At the outset, different pyrolysis methods slow pyrolysis, fast/flash pyrolysis, catalytic pyrolysis, microwave assisted pyrolysis and hydropyrolysis operated for the conversion of various microalgae and cyanobacteria into biochar and bio-oil were reviewed using copious literature. Further, challenges arisen out of using above-said pyrolysis methods were critically highlighted to pave the way to choose an appropriate pyrolysis method for obtaining desirable quantity and quality of bio-oil from algae.